PENGARUH PENGEMBANGAN PRODUK BARU WARDAH TERHADAP KEPUASAN KONSUMEN DI PT. PTI CABANG PALEMBANG - Kemas Welly Angga Permana; Debby Marthalia (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The purpose of this study was to determine the effect of new product development Wardah to customer satisfaction and to determine how much influences to the development of new products Wardah towards customer satisfaction at PT. PTI Palembang. The object of this research was whether the effect of new product development Wardah, with the scope of services provided in the company. The experiment was conducted using descriptive research method analitif, the research methods to gather information about the facts, symptoms, from the factual part of the population (sample) to represent the entire population, and aims to find the relationship between variables. The results of the analysis states on new product development undertaken by Wardah effected to customer satisfaction. This can be seen with a statistical test by using Pearson correlation analysis, that the effect of new product development to customer satisfaction juice products Wardah was very strong as evidenced by the results of calculations that showed that the effect of new product development to customer satisfaction by 0798 with a significant level 0, 60 < 0.78. New product development for variable magnitude of the coefficient of determination was 63.68% and the remaining 36.32% influenced by other factors not examined in this study. From the results of this study found that cosmetics sales growth was also driven by the rising trend in the use of cosmetics by men. In the past they were not interested in buying beauty products and treatments Wardah, but now their interest are pretty high.